THE PECULIARITIES OF PROFESSIONAL DEVELOPMENT IN TRANSFORMATIONAL SOCIETY AND THEIR ROLE IN HUMAN RESOURCES MANAGEMENT - Stepanyan, A.A. (Modern Psychology, 2025)
Global historical developments and globalization processes lead to changes and dynamic development of modern societies. Thus, the concept of transformational society is formed. At the same time there are significant changes in society system, which are: the localization of western models in social fields activities, international integration, formation of new models of public administration and governance, IT investment procedures. The significant social changes have manifestations in the state and private organizations management processes. This leads to changes of the work organization peculiarities and human resources management. Consi- dering the psychological features and competencies of employees as an essential part of organizational management, we have made a research in order to distinguish the peculiarities of personal features and the interrela- tion between them. We have analyzed the correlation of those features bet- ween managers and non-managers. During the research we studied the per- sonal psychological characteristics, motivational orientations and psychologi- cal maturity of the personnel.